Design and Testing of a Flow Measurement System for an Urban Sewage Drain - Gupta S.K.; Singh V.P.; Mishra V.B. (My University, 2025)
A flow-measuring system was developed to measure the flow rate of a river called Assi, a tributary to River Ganges in the city of Varanasi, India. The Assi River carries a huge quantity of sewage water, and thus serves as large sewerage drain for the city. A sewage treatment plant that was under consideration to treat the wastewater discharge into the Ganges needed empirical flow data to establish its design capacity. This gave rise to the installation of a flow-measuring system. The distinctive features of the measuring system, which has potential for application to other areas around the world, are discussed. © 2012 American Society of Civil Engineers.